Mind Over Magnets – How Magnetic Particle Imaging is Changing the Way We Think About the Future of Neuroscience. (15th October 2021) - Makela, Ashley V.; Gaudet, Jeffrey M.; Murrell, Donna H.; Mansfield, James R.; Wintermark, Max; Contag, Christopher H.
Highlights: MPI is highly sensitive, providing the tools to detect disease at early onset or information in minute regions of the brain. MPI has been utilized to image neurological conditions including cancer, inflammation, vasculature and cell therapies. Preclinical findings highlight the potential for future clinical applications to understand and treat neurological disease. Abstract: Magnetic particle imaging (MPI) is an emerging imaging technique, which has the potential to provide the sensitivity, specificity and temporal resolution necessary for novel imaging advances in neurological applications. MPI relies on the detection of superparamagnetic iron-oxide nanoparticles, which allows for visualization and quantification of iron or iron-labeled cells throughout a subject. The combination of these qualities can be used to image many neurological conditions including cancer, inflammatory processes, vascular-related issues and could even focus on cell therapies and theranostics to treat these problems. This review will provide a basic introduction to MPI, discuss the current use of this technology to image neurological conditions, and touch on future applications including the potential for clinical translation.